2003
DOI: 10.3801/iafss.fss.7-221
|View full text |Cite
|
Sign up to set email alerts
|

Brillouin Scattering Based Distributed Fiber Optic Temperature Sensing For Fire Detection

Abstract: This paper presents a distributed fiber optic Brillouin scattering investigation, which involves measuring the Brillouin intensity versus time for real-time temperature measurements. This can be applied in practical fire detection schemes through the use of a threshold temperature that corresponds to the maximum Brillouin intensity. In the experiments, a 11 km fiber length was interrogated by 20 ns pulses (2 m spatial resolution) to monitor the temperature variations in a 10 m fiber region. The corresponding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Recent research has showed that there is a clear relationship between the Brillouin power gain and the fiber temperature [21]. The Brillouin power gain increases with fiber temperature and is maximized when the Brilliouin frequency is equal to the frequency difference between the two lasers for the fiber temperature at a specified fiber location(s).…”
Section: Emerging Sensor Technology 21 Heat Detectorsmentioning
confidence: 99%
“…Recent research has showed that there is a clear relationship between the Brillouin power gain and the fiber temperature [21]. The Brillouin power gain increases with fiber temperature and is maximized when the Brilliouin frequency is equal to the frequency difference between the two lasers for the fiber temperature at a specified fiber location(s).…”
Section: Emerging Sensor Technology 21 Heat Detectorsmentioning
confidence: 99%
“…However, in many applications, sub-centimeter measurement resolutions (or rather spatial resolutions of order ≪10 −4 of the total sensor length) are not necessary, and instead robustness, simplicity, fast sampling times, and low cost are primary concerns. Examples of such cases might be fire detection in buildings, tunnels, etc., 23 leak detection, 24 machines, 25 and perimeter security (or intrusion sensing), 26 to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is mostly seen as a problem in telecommunication, SBS has been used in interesting applications such as slow light [4], amplification [5] and sensing. To date, temperature and strain dependence has been measured in single-mode fiber (SMF), which has led to a variety of distributed sensors [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that SBS is temperature and strain sensitive [6,10], so that it can be used as an effective distributed sensor. Also with the resurgence of interest in MMF for increasing the bandwidth of optical fiber links by the use of individual modes [11], it is important to examine the threshold for stimulated Brillouin scattering for each launched mode.…”
Section: Introductionmentioning
confidence: 99%